Grass pea, Lathyrus sativus L. - Campbell, C.G.; Leibniz Institute of Plant Genetics and Crop Plant Research; International Plant Genetic Resources Institute (1997)
The grass pea (Lathyrus sativus) has over the past decade received increased interest as a plant that is adapted to arid conditions and contains high levels of protein. This monograph describes the genetic resources of grass pea and reviews various aspects of its taxonomy, botany, origin and centres of diversity, properties and uses, characterization, evaluation and conservation, breeding, production, ecology, agronomy, and limitations, prospects and research needs. The activities and remit of the proposed Lathyrus Genetic Resources Network are discussed. Three appendices detail (1) centres holding collections of grass pea, (2) research contacts and (3) acronyms and abbreviations. In addition to a list of references, a further reading list is supplied. (Abstract © CAB ABSTRACTS, CAB International)